ICGenomics: A PROGRAM COMPLEX FOR ANALYSIS OF SYMBOL SEQUENCES IN GENOMICS - Y. L. Orlov; A. O. Bragin; I. V. Medvedeva; K. V. Gunbin; P. S. Demenkov; O. V. Vishnevsky; V. G. Levitsky; D. Y. Oshchepkov; N. L. Podkolodnyy; D. A. Afonnikov; I. Grosse; N. A. Kolchanov (Вавиловский журнал генетики и селекции)
The pilot program complex for analysis of symbol sequences in genomics, ICGenomics, has been designed for storage, mining, and analysis of sequences related to theoretical and applied genomics. ICGenomics enables wet-lab biologists to perform high-quality processing of data in the fields of genomics, biomedicine, and biotechnology. ICGenomics implements both conventional and modern methods for processing, analyzing, and visualizing sequence data. They include novel methods of the processing of initial high-throughput sequencing data. Examples are: ChIP-seq analysis; functional annotation of gene regulatory regions in nucleotide and amino acid sequences; prediction of nucleosome positioning; and structural and functional annotation of proteins, including their allergenicity and evolution features. Application of ICGenomics to the analysis of genomic sequences of the parasite Opisthorchis felineus and to ChIP-seq data on the mouse and human is considered. The system is available at http://www-bionet.sscc.ru/icgenomics.